Capital for the Future : Saving and Investment in an Interdependent World. - Bank, World (Global Development Horizons Ser., 2013)
The gradual acceleration of growth in developing countries is a defining feature of the past two decades. This acceleration came with major shifts in patterns of investment, saving, and capital flows. This second volume in the Global Development Horizons series analyzes these shifts and explores how they may evolve through 2030. Average domestic saving in developing countries stood at 34 percent of their GDP in 2010, up from 24 percent in 1990, while their investment was around 33 percent of their GDP in 2012, up from 26 percent. These trends in saving and investment, along with higher growth r.